Kinetic study of biogas production from anaerobically digested rice straw - Kaur, Maninder; Dhundhara, Sandeep (International Journal of Advances in Applied Sciences, 2025)
Rising concern about environmental protection has demanded prompt researchers’ attention towards alternative renewable energy sources. Thus, biofuel production with biodegradation of crop straws through anaerobic digestion has attracted the attention of the scientific community. However, the lignocellulosic nature of rice straw poses resistance to its disintegration through anaerobic digestion. Aiming to optimize the concentration of sodium hydroxide pretreatment of rice straw for efficient biogas production this study was conducted. For this purpose, the pretreatment was done on rice straw with different concentrations of sodium hydroxide at about 25 °C temperature for 24 hours before subjecting it to anaerobic digestion for biogas production. The 6% sodium hydroxide pretreated rice straw was observed to be resulting in the highest cumulative biogas production which was found to be 56.3% higher than untreated rice straw. In the kinetic study of biogas production, 6% NaOH pretreated rice straw shows the highest biogas production potential at the highest rate of 15.8496 ml/day with a minimum lag period of 0.6758. The experimental study and kinetic study results represent that 6% NaOH pretreated rice straw has the highest biogas production.